Volume 2: Coal, Biomass and Alternative Fuels; Combustion and Fuels; Oil and Gas Applications; Cycle Innovations 1997
DOI: 10.1115/97-gt-439
|View full text |Cite
|
Sign up to set email alerts
|

Mixing of Multiple Jets With a Confined Subsonic Crossflow: Part II — Opposed Rows of Orifices in Rectangular Ducts

Abstract: This paper summarizes experimental and computational results on the mixing of opposed rows of jets with a confined subsonic crossflow in rectangular ducts. The studies from which these results were excerpted investigated flow and geometric variations typical of the complex 3-D flowfield in the combustion chambers in gas turbine engines. The principal observation was that the momentum-flux ratio, J, and the orifice spacing, S/H, were the most significant flow and geometric variables. Jet penetrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Recent NASA-supported studies are summarized in works by Holdeman et al 1,2 for cylindrical and rectangular ducts, respectively. Previous studies, mostly with smaller ori ces in rectangular and annular ducts, are summarized by Holdeman. 3 A summary of previous jetin-cross ow studies (mostly con ned) is given by Margason.…”
Section: Introductionmentioning
confidence: 99%
“…Recent NASA-supported studies are summarized in works by Holdeman et al 1,2 for cylindrical and rectangular ducts, respectively. Previous studies, mostly with smaller ori ces in rectangular and annular ducts, are summarized by Holdeman. 3 A summary of previous jetin-cross ow studies (mostly con ned) is given by Margason.…”
Section: Introductionmentioning
confidence: 99%
“…An extensivelisting of these documented jet-in-cross ow studies performed in the past few decades can be found in Refs. [2][3][4][5]. Note that many of the studies cited in these summaries are of a single jet in an unboundedcross ow or are otherwise inappropriate for direct application.…”
Section: Introductionmentioning
confidence: 99%